The symbolization of a snake and tree among the devotees of the zar spirit in Sudan - Kakouris, Georgios (IJORESH Indonesian Journal of Religion Spirituality and Humanity, 2023)
This paper deals with a symbolic interpretation of the structural position that the snake and the tree possess in the local worship of the zar spirit within the borders of Islamic Sudan. The paper at hand aims to study, via bibliographic research, how the snake Azrag Banda, a manifestation of zar, and his tree-abode are regarded as significant symbols in the Sudanese zar tumbura, a self-nominated Islamic practice and spirit-possession cult with therapeutic functions. The snake Azrag Banda and his tree play a special role in the life of the cult and are meaningful symbols due to the collective historical experience of the Sudani, the devotees of zar tumbura. As it will be shown, the main characteristic of the Sudani Self is a past of slavery and displacement and a present of living on the margins of Sudanese society. In this regard, the current article aims at indicating what the snake entity Azrag Banda and his tree-abode mean for the Sudani. Adopting an emic approach, the snake and the tree will be seen as traditional Sudanese earth symbols, which are considered able to offer protection, heal the historical stigma of slavery, help the subaltern establish their “roots” in the Sudanese ground, and thus upgrade the low social status of the Sudani. In this way, the latter is transformed into free men and genuine landowners.